Thermogravimetric analysis of slow pyrolysis in chicken skin waste. Issue 17 (2nd September 2021) - Anuar, Nur Faradila; Ma'Amor, Azman; Mahmud, Habibun Nabi Muhammad Ekramul; Abdullah, Fatimah Zahara; Alias, Rusmi; Musa, Mohibah; Muhamad, Ernee Noryana
ABSTRACT: Thermogravimetric analysis (TGA) and differential thermal gravimetric (DTG) were used to study the efficiency of slow pyrolysis of chicken skin waste (CSW) through determining the apparent activation energy. CSW was heated from 50°C to 900°C at 5°C/min, 10°C/min, 15°C/min, and 20°C/min. The CSW was further investigated in pyrolysis using a fixed bed reactor where the maximum production of bio-oil was achieved at 550°C. The crude bio-oil products demonstrated different classes of organic and complex mixture of hydrocarbons compound. The proposed decomposition pathway suggested that most CSW was cracked around 340–440°C even at a low heating rate to produce mostly long-chain hydrocarbons.